2007
DOI: 10.1111/j.1365-2362.2007.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

ADMA correlates with portal pressure in patients with compensated cirrhosis

Abstract: These results suggest that ADMA may play a pathophysiological role in portal hypertension by contributing to the relative intrahepatic NO deficiency typical of endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…Adjustments for either Child-Pugh stage or MELD score attenuated the associations of all arginine metabolites with survival, but SDMA and DAS remained significantly predictive of mortality independently of both Child-Pugh stage and MELD score. Our results are in line with previous studies that reported on increased ADMA levels in patients with liver diseases (Mookerjee et al 2007a, b;Richir et al 2008;Siroen et al 2005;Laleman et al 2005;Becker et al 2009;Kasumov et al 2011;Vizzutti et al 2007;Lluch et al 2004Lluch et al , 2006Nijveldt et al 2003aNijveldt et al , 2004Karakurt et al 2009). The present work extends the current knowledge on ADMA and liver dysfunction by confirming previous data on the association of ADMA with Child-Pugh score (Lluch et al 2004), and by demonstrating for the first time that ADMA is positively correlated with the MELD score.…”
Section: Discussionsupporting
confidence: 96%
See 4 more Smart Citations
“…Adjustments for either Child-Pugh stage or MELD score attenuated the associations of all arginine metabolites with survival, but SDMA and DAS remained significantly predictive of mortality independently of both Child-Pugh stage and MELD score. Our results are in line with previous studies that reported on increased ADMA levels in patients with liver diseases (Mookerjee et al 2007a, b;Richir et al 2008;Siroen et al 2005;Laleman et al 2005;Becker et al 2009;Kasumov et al 2011;Vizzutti et al 2007;Lluch et al 2004Lluch et al , 2006Nijveldt et al 2003aNijveldt et al , 2004Karakurt et al 2009). The present work extends the current knowledge on ADMA and liver dysfunction by confirming previous data on the association of ADMA with Child-Pugh score (Lluch et al 2004), and by demonstrating for the first time that ADMA is positively correlated with the MELD score.…”
Section: Discussionsupporting
confidence: 96%
“…ADMA and SDMA are endogenous inhibitors of nitric oxide (NO) synthase (Tsikas et al 2000a, b) and can thereby contribute to intrahepatic NO deficiency, an important factor for the development of portal hypertension (Laleman et al 2005;Vizzutti et al 2007). Previous studies suggest that liver dysfunction is associated with excess ADMA levels due to both, increased ADMA production by high protein methylation and decreased ADMA degradation by low hepatic DDAH activity (Mookerjee et al 2007a;Richir et al 2008;Siroen et al 2005;Laleman et al 2005;Tsikas et al 2003Tsikas et al , 2007Kasumov et al 2011;Vizzutti et al 2007;Becker et al 2009). By contrast, SDMA levels are considered to be mainly determined by renal SDMA excretion; however, findings in 24 patients undergoing hepatic resection suggest that the liver may also contribute to SDMA elimination (Siroen et al 2005).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations